Erratum: Interaction of cochlin and mechanosensitive channel TREK-1 in trabecular meshwork cells influences the regulation of intraocular pressure - Teresia A. Carreon (Nature Portfolio, 2017)
A correction to this article has been published and is linked from the HTML version of this paper. The error has been fixed in the paper.